THREE STRATEGIES OF PROFILING EVENTS IN CAUSATIVE CONSTRUCTION WITH PREFIX PA- IN DHAO - Jermy Imanuel Balukh (Linguistik Indonesia, 2019)
This paper investigates causative constructions in Dhao, which involves the prefix pa-. Dhao is a language spoken by about 3000 people on Ndao Island, Eastern Indonesia. The use of pa- results in three different constructions. First, a construction with a single verbal predicate in which pa- is fused with the base verb expressing the cause and caused events. Second, the pa-derived verb requires a lexical verb to precede it resulting in an SVC. Thus, the events profiled are arranged into separate components. Third, the construction is periphrastic, where the pa-derived verb appears in the subordinate clause designating result state of the causee, while the causation is expressed by a lexical verb in the main clause. These three different strategies are employed to express different events profiled in the causativized construction.